Out of this world - Lloyd, Brendan (Fremantle, Western Australia : Vivid Publishing, 2015)
"Have you ever considered spirituality but decided you couldn’t make sense of all the jargon? You’re not alone. Why settle for ‘New Age’ when you don’t understand the Age-Old? In this book, you’ll discover real experiences and real insight – nothing fictional, or second-hand (except maybe this book one day). If you don’t think (even slightly) differently after reading this book, either you’re not thinking enough, or you didn’t stop and think ‘Why are we here?’ To quote the original Matrix film, ‘Free your mind’; discover possibilities you thought were impossible, when you already knew the Mission was Impossible. But this one doesn’t come with popcorn! I’m not here to tell you to ‘look within’, or that ‘the Kingdom of God is within’, I’m here to tell you – look for God, because the delusion is to believe in nothing at all!"--Back cover.
Keywords: God; God -- Knowableness; Spiritual direction; Experience (Religion).; Australian